Ecological Approach to Unravel Streptomycete Diversity as an Unsurpassed Sources of Natural Bioactive Products - LANGKAH SEMBIRING; MICHAEL GOODFELLOW (Microbiology Indonesia, 2008)
Search and discovery for natural bioactive products have been so important to control the emergence of antibiotic resistant microbial pathogens. Therefore, novel microorganisms that produce such metabolites is extremely needed. The capacity of members of the genus Streptomyces to produce commercially significant bioactive metabolites, notably antibiotics remains unsurpassed. However, it is acknowledged that discovering commercially useful secondary metabolites from streptomycetes is becoming more difficult due to lack of knowledge on the ecology and complexity of streptomycete systematics. In fact, those are fundamental aspects for developing strategy and method for isolation. In order to devise an appropriate program for successful selective isolation of sreptomycetes, it is fundamentally important to understand their occurance and activity in nature. A multistep extraction procedure designed for representative sampling, called dispersion, and differential centrifugation technique in combination with the incorporation of antibiotics into isolation media has become one of the most important selective method for the isolation of streptomycetes from natural habitats. The availability of new procedures to selectively isolate representative of streptomycetes from natural habitats opens up the possibility to determine the extent of streptomycete diversity from various habitats. Hence, the capacity of well characterized streptomycete isolates to produce commercial novel active metabolites could be further assessed appropriately.